Perencanaan Strategis Sistem dan Teknologi Informasi pada RSIA Putri Surabaya Berdasarkan Metode Ward and Peppard - novalita, caroline patricia; Maulana, Yoppy Mirza; Ayuningtyas, Ayuningtyas Ayuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
RSIA Putri Surabaya is a hospital engaged in health services. The business process on RSIA Putri Surabaya has problems that the application of STI on RSIA Putri Surabaya is currently not aligned with the business strategy and based on the needs of each department, the company has not determined and grouping priority scale on STI that will be applied, the IT facilities can’t be useful for the company, the consequences is wasted cost budget. The solution provided is to create a document strategic planning system and information technology at RSIA Putri Surabaya with Ward and Peppard method.